Tax Policy on the Growth and Competitiveness of SMEs in the National Economy Sector - Anastasia, Maria (Advances in Taxation Research, 2025)
Purpose: This study examines the impact of tax policies on the growth and competitiveness of SMEs within the national economy. It aims to identify how well-structured tax frameworks, including incentives and simplified systems, can support SME performance and adaptation in an increasingly digital and globalized environment. Research Design and Methodology: Using a qualitative approach, this study employs a Systematic Literature Review (SLR) methodology to synthesize and critically analyze existing research on SME tax policy. Agency theory is the lens through which to explore the alignment between tax policy design and SME compliance and growth dynamics. Findings and Discussion: The findings reveal that well-designed tax policies significantly contribute to SME growth by fostering investment capacity, promoting innovation, and reducing administrative burdens. Simplified tax systems and digital tax platforms enhance operational efficiency and competitiveness, enabling SMEs to navigate domestic and international markets more effectively. However, challenges such as information asymmetry, limited resource access, and bureaucratic inefficiencies remain significant barriers. The study highlights the need for adaptive and inclusive tax policies that align with SMEs' unique operational realities, emphasizing the dual role of tax systems as enablers of growth and compliance mechanisms. Implications: This research provides actionable insights for policymakers to design effective tax frameworks that support SME growth while fostering compliance. It offers practitioners managerial guidance on leveraging tax incentives and navigating regulatory systems. By addressing the challenges identified, this study contributes to sustainable economic development by empowering SMEs to thrive in competitive markets.